2021
DOI: 10.1002/jgh3.12602
|View full text |Cite
|
Sign up to set email alerts
|

Consensus statements and recommendations on the management of mild‐to‐moderate gastroesophageal reflux disease in the Southeast Asian region

Abstract: This paper reports the proceedings from the first consensus meeting on the management of mild‐to‐moderate gastroesophageal reflux disease (GERD) in the Southeast Asian (SEA) region. Seventeen statements were drawn up by a steering committee that focused on epidemiology, mechanism of action, diagnostic investigations, and treatment. Voting on the recommendations used the Delphi method with two rounds of voting among the 10 panel members. The consensus panel agreed that GERD is mostly a mild disease in the SEA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 97 publications
(112 reference statements)
0
8
0
1
Order By: Relevance
“…However, the only measures that have been shown to be beneficial on the part of obese patient is weight loss [37]. Weight loss is strongly recommended in overweight or obese GERD patients to improve the reflux symptoms [6,36]. A prospective cohort study has found that in GERD subjects with overweight and obesity, weight reduction was significantly decreased the overall prevalence of GERD with significant improvement in overall symptoms scoring, compared to baseline [38].…”
Section: Weight Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the only measures that have been shown to be beneficial on the part of obese patient is weight loss [37]. Weight loss is strongly recommended in overweight or obese GERD patients to improve the reflux symptoms [6,36]. A prospective cohort study has found that in GERD subjects with overweight and obesity, weight reduction was significantly decreased the overall prevalence of GERD with significant improvement in overall symptoms scoring, compared to baseline [38].…”
Section: Weight Reductionmentioning
confidence: 99%
“…Recent evidence showed a rising prevalence of GERD and it was estimated 1.03 billion individuals are suffering from GERD globally [4,5]. GERD has also become more prevalent nowadays in a previously uncommon region, such as Asia Pacific [6]. Excessive body weight is one of the multiple conditions that contribute to this escalation in GERD cases [7].…”
Section: Introductionmentioning
confidence: 99%
“…За результатами першої консенсусної зустрічі щодо лікування Герх у регіоні Південно-східної азії альгінати рекомендували як препарати 1-ї лінії для пацієнтів із Герх легкого та середнього ступеня тяжкості, а також як допоміжну терапію, коли симптоми Герх лише частково реагували на ІПП [47].…”
Section: рисунок 3 схема взаємного обтяження Covid-19 таunclassified
“…The overall prevalence of GERD in adults is 13.3%, with a higher rate of 19.6% in Central America and 22.1% in South Asia. [ 3 ] GERD can result in diminished health-related quality of life, and potential long-term treatment can consume substantial health care resources.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 , 8 ] Simultaneously, the global prevalence of GERD has also been reported to be increased. [ 3 , 9 ] CAS and GERD share common risk factors and a common neurological pathway for their corresponding functions, which can make GERD and CAS interact and mutually reinforce each other. [ 10 , 11 ] On the one hand, gastroesophageal acid reflux via the vagal reflex may cause coronary hypoperfusion.…”
Section: Introductionmentioning
confidence: 99%